Non‐clinical safety assessment of single and repeated administration of gE/AS01 zoster vaccine in rabbits. Issue 2 (12th May 2016) - Giordano, Giulia; Segal, Lawrence; Prinsen, Menk; Wijnands, Marcel V. W.; Garçon, Nathalie; Destexhe, Eric
Abstract: HZ/su is an investigational recombinant subunit vaccine for the prevention of shingles, a disease resulting from the reactivation of varicella zoster virus. The vaccine is composed of recombinant varicella zoster virus glycoprotein E (gE), and liposome‐based Adjuvant System AS01. To evaluate the potential local and systemic effects of this vaccine, three studies were performed in rabbits. In the first two studies, rabbits received a single intramuscular (IM; study 1) or subcutaneous (SC; study 2) dose of gE/AS01, AS01 alone (in study 2 only) or saline, and the local tolerance was evaluated up to 3 days after administration. Under these conditions, only local inflammatory reactions at the injection sites were detected by microscopic evaluation. In the third study, gE/AS01, AS01 alone or saline, were injected SC or IM on four occasions at 2 week intervals. General health status, local tolerance, ophthalmology, haematology and blood chemistry parameters were monitored. Macroscopic and microscopic evaluations were performed after termination of the study. The only treatment‐related changes included a transient increase in neutrophils, C‐reactive protein and fibrinogen levels and microscopic signs of inflammation at the injection sites, which are expected observations related to the elicited inflammatory reaction. The SC and IM routes of administration produced similar systemic effects. However, microscopic findings at the injection sites differed. One month after the last injection, recovery was complete in all groups. In conclusion, the single and repeated SC and IM administration of the gE/AS01 vaccine were locally and systemically well‐tolerated in rabbits and support the clinical development of the vaccine. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : HZ/su is an investigational recombinant subunit vaccine for the prevention of shingles, a disease resulting from reactivation of the varicella zoster virus. The vaccine is composed of recombinant varicella zoster virus glycoprotein E (gE), and liposome‐based adjuvant system AS01. We evaluated the potential local and systemic effects of this vaccine in rabbits and observed that single and repeated SC and IM administration of the gE/AS01 vaccine were locally and systemically well‐tolerated, which support the clinical development of the vaccine.